2018
DOI: 10.1053/j.gastro.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of C1galt1 Gene Promotes Development and Metastasis of Pancreatic Adenocarcinomas in Mice

Abstract: In studies of KPC mice with disruption of C1galt1, we found that loss of C1galt1 promotes development of aggressive PDACs and increased metastasis. Knockout of C1galt1 leads to increased tumorigenicity and truncation of O-glycosylation on MUC16, which could contribute to increased aggressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 47 publications
(49 reference statements)
6
87
0
Order By: Relevance
“…For example, it has been reported that disruption of either Cosmc or T-synthase equally induced aberrant O-glycosylation and significantly promoted malignant behaviors in pancreatic cancer. 18,19 Liu et al also showed that Cosmc deficiency in human colorectal cancer cells markedly enhanced cellular growth and metastasis. 41 Conversely, several recent studies unexpectedly found that loss of T-synthase, but not Cosmc, resulted in Tn antigen expression and subsequently delayed tumor development including breast, head and neck, and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, it has been reported that disruption of either Cosmc or T-synthase equally induced aberrant O-glycosylation and significantly promoted malignant behaviors in pancreatic cancer. 18,19 Liu et al also showed that Cosmc deficiency in human colorectal cancer cells markedly enhanced cellular growth and metastasis. 41 Conversely, several recent studies unexpectedly found that loss of T-synthase, but not Cosmc, resulted in Tn antigen expression and subsequently delayed tumor development including breast, head and neck, and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…15,16 However, the precise role of Tn antigen (representative of abnormal O-glycosylation) in tumor progression, particularly breast cancer, is largely unclear. The prevailing studies supported a tumorpromoting role for aberrant O-glycosylation in a broad range of human cancers, including pancreatic, colorectal, and gastric cancer, [17][18][19][20] whereas several recent reports indicated rather an opposite effect of aberrant O-glycosylation, which was shown to delay tumor development in breast, liver, and head and neck cancers. [21][22][23] Overall, there is much to be learned about the impact of aberrant O-glycosylation on breast cancer development.…”
Section: Introductionmentioning
confidence: 98%
“…We recently published a role of C1GALT1 in pancreatic ductal carcinoma using in vitro and in vivo KO models [35]. The deletion of C1GALT1 caused an aggressive phenotype in the context of pancreatic ductal adenocarcinoma.…”
Section: Core-1 Synthase Loss Aggravates Pancreatic Cancermentioning
confidence: 99%
“…Aberrant glycosylation is associated with tumor initiation, development, and metastasis. The expression of TACAs like Tn, sTn, T, sT (truncated) and sialyl Lewis a (sLe a ), sialyl Lewis x (sLe x ) (de novo; neo-synthesis) are especially implicated in tumor formation and metastasis in many cancers, including PC [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of truncated O -glycans induced oncogenic signaling in PC; however, expression of core-3 derived O -glycans (extended structures) was shown to inhibit tumor growth and metastasis [ 18 , 19 ]. In our recent study, we demonstrated that the crossing of C1galt1 floxed mice with Kras G12D ; p53 R172H ; Pdx-1-Cre mice resulted in elevated synthesis of truncated O -linked glycans promoting development of aggressive PDAC with increased metastasis [ 17 ]. De-regulated mucin expression (MUC1, MUC4, MUC5AC, MUC16; majorly O -linked glycoprotein) has been implicated in PC development, metastasis, and chemoresistance [ 16 , 20 24 ].…”
Section: Introductionmentioning
confidence: 99%